Gender Speech Differences in Politeness Strategies Among University Students: The Malaysian Context - Ali Hassan, Mohamed Taha (2002)
According to Lakoff (1975), women use more politeness strategies than men because of their inferior position in a society. Furthermore, Lakoff indicated that women also use different strategies in order to talk in less assertive ways such as with the use of tag questions, indirect statements, and discourse particles. Many studies which have been conducted, based on her claims, showed inconsistent findings. Commentators such as Romaine (1994), Holmes (1995), Gordon (1997), Cameron (1992), Tannen (1993), and Wardhaugh (1998) are of the idea that the use of politeness strategies is dependent on many social factors that are reflected in the use of the language. Meanwhile, studies on gender speech differences, especially those concerning the use of politeness strategies, have been conducted in different contexts and fields. However, few such studies have been conducted in the Malaysian context and none so far has focused on university students. In carrying out the study of gender speech differences in politeness strategies among university students, the researcher utilizes a qualitative as well as a quantitative design. The study sample consisted of the students of BA English language programme at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia. The data was collected via recordings of cross-gender conversations and questionnaires. The findings suggest that females tend to use more politeness strategies than males at the university level in the Malaysian context, which lend support to Lakoff's (1975) claim that women use more politeness strategies than men. However, not all of the reasons for using politeness strategies support Lakoffs claim that by using politeness strategies, women avoid straightforward statements due to their inferior positions in the society. Politeness strategies appeared to be mostly effected through the use of discourse particles. Additionally, the use of tag questions a s politeness strategies is more frequent among females, and they mainly use them as negative strategies. It is also noted that females use more direct statements to effect politeness strategies and mainly use them positively, which is not in line with Lakoffs claim. The discourse particles are mainly used by university students as negative politeness strategies. However, a comparison of the results also showed that males use more negative politeness strategies than females. Another finding is that a single strategy could be used to function both positively and negatively. It is also observed that the most frequently used discourse particles by the respondents are you know, I think, and yah. Tag questions used as politeness strategies are the forms right and ok. Most of the direct statements used as positive politeness strategies are the would clauses. The study highlights some points of gender speech differences in politeness strategies among university students in the Malaysian context.